Caffeic Acid Supplement Alleviates Colonic Inflammation and Oxidative Stress Potentially Through Improved Gut Microbiota Community in Mice - Wan, Fan; Zhong, Ruqing; Wang, Mengyu; Zhou, Yexun; Chen, Yuxia; Yi, Bao; Hou, Fujiang; Liu, Lei; Zhao, Yong; Chen, Liang; Zhang, Hongfu (Frontiers in Microbiology, 2021)
Caffeic acid (CA) is one of the major phenolic acids of coffee with multiple biological activities. Our previous study found that 500 mg/kg chlorogenic acid (CGA) had the potential capacity of alleviating colonic inflammation. Moreover, CGA can be degraded into caffeic acid (CA) by the gut microbiota in the colon. Therefore, we hypothesize that CA can exert protective effects on colonic inflammation. To test the hypothesis, 251 mg/kg CA was supplemented to DSS-induced colitis mice. The results showed that CA treatment recovered DSS-induced disease activity index (DAI), colon length, and histopathology scores of colon tissue. Additionally, CA treatment significantly decreased pro-inflammatory cytokines and malondialdehyde (MDA) levels and increased the level of IL-10, total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) in serum. qPCR results indicated that CA treatment dramatically downregulated mRNA expression of IL-1β, IL-6, and TNF-α as well as upregulated SOD1, GPX1, GPX2, CAT, and IL-10. In addition, CA supplementation significantly increased mRNA expression of Nrf-2, HO-1, and NQO1, which showed its antioxidant and anti-inflammatory capacities potentially by activating Nrf-2/HO-1 pathway. Moreover, CA supplementation prevented gut barrier damage by enhancing Occludin gene expression. Furthermore, CA supplementation altered the gut microbiome composition by decreasing the relative abundance of Bacteroides and Turicibacter, and enhancing the relative abundance of Alistipes and Dubosiella. Meanwhile, CA supplementation increasing the abundance of Dubosiella and Akkermansia. In conclusion, CA supplementation could effectively alleviate DSS-induced colitis by improving defense against oxidative stress and inflammatory response.